TRANSMISSION OF ETHNIC CULTURE: THEORETICAL AND PRACTICAL ASPECTS - Stonkuvienė, Irena (Acta Paedagogica Vilnensia, 2011)
Following insights of representatives of various sciences (M. Mead; L. Cavalli-Sforza and M. Feldman, G. Trommsdorff, M. Lukšienė and others), the article discusses models for cultural transition, perceived not only as anthropological models but also as those of educational construct. Interdisciplinary approach allowed for a deeper penetration into links between education and culture and contributed to drawing up of guidelines for methodological empiric research.Following the results of the research “Identity, Cultural Transmission and National Education” conducted by a group of VUresearchers in 2010, the article analyses the situation of the main mechanism of culture transmission, i.e., tradition, in Lithuania in the 21st century. Attitudes of school learners-teachers and members of family representing different generations (children-parents-grandparents) to ethnic culture and traditions are also discussed.It has been revealed that natural expression of traditions and customs has lost a broader communal component and is mainly linked with the family. It can be stated that the family is undoubtedly the main institution in children’s education, which has the biggest influence on transfer of ethno-cultural values. The hypotheses that vertical transmission (children – parents – grandparents) yields the ground to horizontal (peers, environment) or oblique transmission (school, other institutions) and that technologies replace traditional authorities for the young generation change were negated: school learners in the survey perceive internet and other media only as more accessible and time-saving sources of information.
Keywords: cultural transmission; ethnic culture; tradition